Examining The Effects Of Education On Social Exclusion, Multidimensional Poverty, And Income Poverty - Neelu Kumari; Dr. Peeyush Kr. Panday (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The critical role of education in influencing economic growth and social advancement brings transformative potential in eradicating issues of social exclusion, multidimensional poverty, and income poverty. This paper focuses on the impact of education within these three dimensions specifically in the National Capital Region. In applying a deductive research method, the study will synthesize both primary and secondary sources of data. For foundation, government and international organization supplied secondary data of socioeconomic indicators. Through surveys and interviews conducted with 200 respondents having diversity in their age and education group, primary data has been collected. Analysis for correlation shows statistical measures for descriptive statistics, which depict significant relationships of educational attainment variables with outcomes of economic performances. Conclusively, gross enrolment ratio and literacy rates appeared to have a positive co-relation with the incidence of poverty and income distribution of households. The results therefore emphasize the need for improved access to and quality of education as a way to minimize socioeconomic disparities and increase social cohesion.